1981
DOI: 10.1063/1.441544
|View full text |Cite
|
Sign up to set email alerts
|

Site distribution studies of Rh supported on Al2O3—An infrared study of chemisorbed CO

Abstract: Using infrared spectroscopy, chemisorbed CO has been employed as a surface probe to observe differences in Rh site distributions on Al2O3-supported Rh. It has been found that higher loadings of Rh lead to Rh site distributions resembling those found on Rh(111) single crystals, whereas low Rh loadings produce isolated Rh sites preferentially. The isolated Rh sites yield infrared spectra characteristic of a species Rh(CO)2. Chemisorption of oxygen onto the CO-covered surface effectively eliminates crystalline Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
77
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(93 citation statements)
references
References 35 publications
15
77
1
Order By: Relevance
“…3D). Similar qualitative behavior has been observed on supported catalyst (5,6,8) and surface science studies (4, 34) of supported Rh particles, which have demonstrated that larger catalyst loadings (likely associated with larger particles sizes) exhibit resistance to dispersion. Thus, the nature of Rh particle dispersion and CO surface adsorbates under elevated pressures, depend on both initial Rh particle size and CO pressure at a given temperature.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…3D). Similar qualitative behavior has been observed on supported catalyst (5,6,8) and surface science studies (4, 34) of supported Rh particles, which have demonstrated that larger catalyst loadings (likely associated with larger particles sizes) exhibit resistance to dispersion. Thus, the nature of Rh particle dispersion and CO surface adsorbates under elevated pressures, depend on both initial Rh particle size and CO pressure at a given temperature.…”
Section: Discussionsupporting
confidence: 58%
“…For example, elevated pressure CO ambients have been shown to oxidatively disrupt and disperse Rh nanoparticles, creating highly dispersed gem-dicarbonyl species RhðCOÞ 2 on oxide supports (1)(2)(3)(5)(6)(7)(8). Under elevated pressure (CO∕H 2 ) and (CO 2 ∕H 2 ) hydrogenation reaction conditions, Rh(CO)H carbonyl hydride species can also be formed (3,(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…This trend was the same as that observed for Rh _ P/SiO2. TiO2 is well k n ow n t o b e m o r e r e d u c i b l e t h a n o t h e r m e t a l oxides 37), 38) . Thus, the large peak observed at 540 would be attributed to the reduction of phosphate and TiO2 support.…”
Section: (Iv) (B)mentioning
confidence: 99%
“…Assuming that CO molecules are linearly adsorbed onto Rh atom, Rh dispersion in Rh/Al2O3 catalyst reduced at 400 was about 1.3. After CO was adsorbed on Rh/ Al2O3 catalyst with high dispersion, the Rh(CO)2 species was identified by infrared spectroscopy 38) . Thus, the remarkable CO uptake of Rh/Al2O3 could be explained by the formation of Rh(CO)2 species.…”
Section: Co Adsorption On Rh/mox and Rh-p/moxmentioning
confidence: 99%
“…The peaks observed after calcination can similarly be attributed to linearly bound CO to Rh of oxidation state 0 (~2070 cm -1 ) or 1 (~2100 cm -1 ) and after reduction only linear bound CO on zero valent Rh is present. [47][48][49][50][51][52][53] This change in available binding sites in schematically represented in Figure 8(A).…”
Section: Diffuse Reflectance Infrared Spectroscopymentioning
confidence: 99%